S-Dimensional Assets Portfolio Evaluation - Copertari, Luis F (International Journal of Business, Economics and Management, 2014)
An approach to calculate the upper limit to any given portfolio with s assets (corporate stocks or government bonds) in it is provided, which does not require the relative weight of each asset in the portfolio. The value obtained is contrasted with the traditional weighting approach to calculate the portfolio’s value. The process followed is the scientific method, starting with observation and hypothesis and after analyzing two examples, a synthesis is performed by generalizing the concepts and the main thesis that the Pythagorean approach here proposed constitutes an upper limit for the portfolio’s value.